Examples

Example 1

Example 2

Example 3

Example 4 Important

Example 5

Example 6

Example 7

Example 8 Important

Example 9 Important

Example 10

Example 11 Important

Example 12 You are here

Example 13 Important

Example 14

Example 15

Example 16 Important

Example 17

Example 18 Important

Example 19

Example 20 Important

Example 21 Important

Example 22

Example 23 Important

Example 24

Example 25 Important

Example 26 Important

Example 27

Example 28 Important

Example 29 Important

Example 30 Important

Example 31 Important

Example 32 Important

Example 33 Important

Example 34 Important

Example 35

Example 36 Important

Example 37

Question 1 Deleted for CBSE Board 2024 Exams

Question 2 Deleted for CBSE Board 2024 Exams

Question 3 Deleted for CBSE Board 2024 Exams

Question 4 Important Deleted for CBSE Board 2024 Exams

Question 5 Deleted for CBSE Board 2024 Exams

Question 6 Deleted for CBSE Board 2024 Exams

Question 7 Deleted for CBSE Board 2024 Exams

Question 8 Deleted for CBSE Board 2024 Exams

Question 9 Deleted for CBSE Board 2024 Exams

Question 10 Deleted for CBSE Board 2024 Exams

Question 11 Deleted for CBSE Board 2024 Exams

Question 12 Deleted for CBSE Board 2024 Exams

Question 13 Important Deleted for CBSE Board 2024 Exams

Question 14 Important Deleted for CBSE Board 2024 Exams

Last updated at April 8, 2024 by Teachoo

Example 12 Find intervals in which the function given by f (x) = sin 3x, x, β [0, π/2] is (a) increasing (b) decreasing. f(π₯) = sin 3π₯ where π₯ β [0 ,π/2] Finding fβ(x) fβ(π₯) = π(sinβ‘3π₯ )/ππ₯ fβ(π₯) = cos 3π₯ Γ 3 fβ(π) = 3. cos 3π Putting fβ(π) = 0 3 cos 3π₯ = 0 cos 3π₯ = 0 We know that cos ΞΈ = 0 When ΞΈ = π/2 & 3π/2 So, for cos 3π = 0 3π₯ = π/2 & 3π₯ = 3π/2 π₯ = π/(2 Γ3) & π₯ = 3π/(2 Γ 3) π = π /π & π = π /π Since π₯ = π/6 β [π ,π /π] & π₯ = π/2 β [π,π /π] β΄ Both values of π₯ are valid Plotting points on number line So, point π₯ = π/6 divides the interval into two disjoint intervals [0 ,π/6) and (π/6, π/2] Checking sign of fβ(π) fβ(π₯) = 3. cos 3π₯ Case 1: For π β (π ,π /π) 0<π₯<π/6 3 Γ 0<3π₯<3π/6 π<ππ<π /π So when π₯ β (0 ,π/6), then 3π₯ β (0 , π/2) We know that cos π½>π for π½ β (π , π /π) cos 3x >0 for 3x β (0 , π/2) cos 3x >0 for x β (0 , π/6) 3 cos 3x >0 for x β (0 , π/6) πβ²(π)>π for x β (0 , π/6) Since fβ(0) = 3 and fβ(π /π) = 0 Therefore, fβ(x) β₯ 0 for π₯ β [0 , π/6] Thus, f(x) is increasing for π₯ β [0 , π/6] Case 2: For π β (π /π, π /π) π/6<π₯<π/2 3 Γ π/6<3π₯<3π/2 π /π<ππ<ππ /π So when π₯ β(π/6 , π/2), then 3π₯ β (π/2 , 3π/2) We know that, cos π<0 for π β (π/2 , 3π/2) cos 3π₯<0 for 3π₯ β (π/2 , 3π/2) cos 3π₯<0 for π₯ β (π/6 , π/2) 3 cos 3π₯<0 for π₯ β (π/6 , π/2) fβ(x) <π for π₯ β (π/6 , π/2) Since fβ(π /π) = 0 and fβ(π /π) = 0 Therefore fβ(x) β€ 0 for π₯ β [π/6,π/2] Thus, f(x) is decreasing for π₯ β [π/6,π/2] Thus, f(x) is increasing for π β [π , π /π] & f(x) is decreasing for π β [π /π , π /π]